The centrality of temperament to the research domain criteria (RDoC): The earliest building blocks of psychopathology. (December 2021) - Ostlund, Brendan; Myruski, Sarah; Buss, Kristin; Pérez-Edgar, Koraly E.
Abstract: The research domain criteria (RDoC) is an innovative approach designed to explore dimensions of human behavior. The aim of this approach is to move beyond the limits of psychiatric categories in the hope of aligning the identification of psychological health and dysfunction with clinical neuroscience. Despite its contributions to adult psychopathology research, RDoC undervalues ontogenetic development, which circumscribes our understanding of the etiologies, trajectories, and maintaining mechanisms of psychopathology risk. In this paper, we argue that integrating temperament research into the RDoC framework will advance our understanding of the mechanistic origins of psychopathology beginning in infancy. In illustrating this approach, we propose the incorporation of core principles of temperament theories into a new "life span considerations" subsection as one option for infusing development into the RDoC matrix. In doing so, researchers and clinicians may ultimately have the tools necessary to support emotional development and reduce a young child's likelihood of psychological dysfunction beginning in the first years of life.